2012
DOI: 10.1007/s10869-011-9255-0
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor Workplace Stress and Abusive Supervision: The Buffering Effect of Exercise

Abstract: Purpose We examine how supervisor stress is associated with employee-rated abusive supervision. In addition, we test the premise that higher levels of physical exercise by supervisors can buffer the negative effects of stress on their relationship with their subordinates. Design/Methodology/Approach A matched sample of 98 employed individuals and their direct supervisors was used to test our hypotheses. Findings Results suggest that increased levels of supervisor-reported stress are related to the increased ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 62 publications
8
119
0
2
Order By: Relevance
“…In other research, Burton, Hoobler, and Scheuer () reported that increased stress experienced by the supervisor also increases the likelihood of engaging in behaviors perceived by subordinates as abusive. Similarly, in an investigation of individual differences associated with abusive supervision, Kiazad, Restubog, Zagencyzk, Kiewitz, and Tang () found that subordinate perceptions of abusive supervision are positively associated with supervisor Machiavellianism.…”
Section: High‐performance Work Practicesmentioning
confidence: 94%
“…In other research, Burton, Hoobler, and Scheuer () reported that increased stress experienced by the supervisor also increases the likelihood of engaging in behaviors perceived by subordinates as abusive. Similarly, in an investigation of individual differences associated with abusive supervision, Kiazad, Restubog, Zagencyzk, Kiewitz, and Tang () found that subordinate perceptions of abusive supervision are positively associated with supervisor Machiavellianism.…”
Section: High‐performance Work Practicesmentioning
confidence: 94%
“…The shortened version was previously used by Jamal and Baba (). This scale was used because of its good psychometric properties as reported in recent studies conducted in Western settings (Burton, Hoobler, & Scheuer, ; Hunter, & Thatcher, ) and in Pakistan (Jamal, , ). The items include “Sometimes when I think about my job I get a tight feeling in my chest” and “I have too much work and too little time to do it in.” The reliability of this scale is α = .71.…”
Section: Methodsmentioning
confidence: 99%
“…For example, abusive supervision may be a response to perceptions of mistreatment by employers (Bushman et al, 2005;Pedersen, Gonzales, & Miller, 2000). Supervisors who are assigned to achieve exceedingly difficult goals tend to feel angry and anxious, and they may accordingly direct abusive behavior at their subordinates (Mawritz, Folger et al,2014;Burton, Hoobler, & Scheuer, 2012;Harris, Harvey, & Kacmar, 2011;Mawritz, Dust et al, 2014). Some studies have also suggested that abusive supervision emerges as a behavior that is learned from upper-level leaders (e.g., Liu et al, 2012).…”
Section: Theoretical Propositionsmentioning
confidence: 99%